Invited hauntings in site-specific performance and poetry: The Asylum Project. Issue 3 (3rd July 2018) - Kuppers, Petra
ABSTRACT: This field report from The Asylum Project, an Olimpias disability culture experiment, centres non-mainstream experiences of space in two Michigan performances, accessing extrasensory experiences as a creative form. How can we witness and amplify histories of intersected violence and emergent forms of healing? How can we invite hauntings? In community performance practices, we address the infrastructures that allow us access to be together. We ask: where is asylum? What is access? The methods of this essay include experimentation with different writing formats, exploring poetry as a way of compressing and layering somatic experience and performance sensing.